Arteriovenous malformations in the neonatal period: case report and literature review - Mariana C. Abreu; Joana Pinto; Gustavo Rocha; Maria Garcia; Maria do Bom-Sucesso; António Miguel Madureira; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2020)
Congenital vascular anomalies are a heterogeneous group of lesions, subdivided into vascular tumors and vascular malformations. Incorrect nomenclature and misdiagnoses are frequent. Arteriovenous malformations (AVM) are potentially the more aggressive type of vascular malformation. They are formed by a complex network of malformed arteries and veins without intervening capillary bed resulting in arteriovenous shunting. The clinical presentation ranges from tissue swelling to serious clinical issues, as right heart failure. We report the case of a female newborn affected by an AVM stage IV of Schobinger, evidenced in the immediate neonatal period, despite the lack of prenatal diagnosis. She underwent two endovascular embolizations procedures with Onyx 18®, with effective devascularization of the AVM. Although advantageous, embolization is a challenging procedure and the risks are real. Our patient experienced a life-threatening hemorrhage a few days after the first embolization. We considered that complete devascularization of the AVM was achieved after two embolization procedures. At 14 months old, she underwent surgery for resection of residual AVM, with fast postoperative recovery. Currently, she is 17 months old, and no AVM recidive occur until now. We report a clinical case that evidences the difficulties of approaching an AVM Schobinger stage IV in the neonatal period. We also present a review of the literature on vascular anomalies with special attention to AVM.